Pengaruh Kualitas Pelayanan dan Budaya Perusahaan terhadap Kepuasan Nasabah pada PT Bank Sulutgo Cabang Surabaya - Ira Rahmawati; Iswati Iswati (Jurnal Manajemen Bisnis Era Digital, 2025)
This study employed a quantitative survey approach to know the effect of service quality and corporate culture on customer satisfaction at PT Bank SulutGo, Surabaya branch. The sample consisted of 94 customers selected through purposive sampling. Data were collected via structured questionnaires and analyzed using multiple linear regression. The multiple regression analysis results showed a coefficient of determination (R²) of 0,530, indicating that the two independent variables together explained 53% of the variable in customer satisfaction. The F-test yielded a value of 53,378 with a p-value of 0,000 (p < 0,05), indicating that the regression model was jointly significant and that service quality and corporate culture together influence customer satisfaction. Partial t-tests showed that the Service Quality variable (X1) significantly affected customer satisfaction with a t-value of 2,227 and a p-value of 0,028 (p < 0.05). Similarly, the Corporate Culture variable (X2) also significantly affected customer satisfaction with a t-value of 4,032 and a p-value of 0.000 (p < 0.05). These findings indicate that higher customer perceptions of service quality and corporate culture lead to higher satisfaction levels. Partial t-tests further revealed that both independent variables significantly affected customer satisfaction. The Service Quality variable (X1) had a significant effect on customer satisfaction, with a t-value of 2.227 and a p-value of 0.028 (p < 0.05). Similarly, the Corporate Culture variable (X2) also had a significant impact, with a t-value of 4.032 and a p-value of 0.000 (p < 0.05). These findings highlight the importance of both service quality and corporate culture in shaping customer satisfaction. The results suggest that improving service quality and fostering a positive corporate culture can significantly enhance customer satisfaction, which is critical in maintaining customer loyalty and competitive advantage in the banking sector.